1984
DOI: 10.1159/000284077
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine and Nonbenzodiazepine Anxiolytics

Abstract: A review of anxiolytic drugs is presented, including ethyl alcohol, barbiturates, diphenylmethane derivatives, glycerol and propanediol derivatives, antipsychotics, and anti-depressants. Focus on the benzodiazepines and their metabolism and method of action follows. The newest two groups are then reviewed: triazolobenzodiazepines and azaspirodecanediones. The first member of this latter group, buspirone, is then reviewed in detail including the author’s personal studies of the drug. The fact that it appears no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…Thus, the doses of zopiclone, triazolam, and nitrazepam we used are thought to be equivalent to 20 Tada/Sato/Sakai/Ueda/Kasamo/Kojima Effects of Hypnotics on Standing Steadiness Previous investigators have reported weak musclerelaxant effects of zopiclone as compared to classical ben zodiazepines in mice, rats, and cats. For instance, the muscle-relaxant effects of zopiclone were approximately 4-80 times less potent than those of nitrazepam in mice and rats [15,16], and 3.5-5 times less potent than those of diazepam in mice, rats, or cats [1], However, the present preliminary data indicating stronger muscle-relaxant ac tivities of zopiclone than of nitrazepam in humans do not support these previous animal experiments. Pharmacoki netic differences between zopiclone and nitrazepam do not seem to explain the differences between studies since our previous pharmacokinetic-dynamic study of nitraze pam indicated that peak effects of nitrazepam were ob tained at 1 and 2 h after drug administration [6,17], Thus, there seem to be great species differences in terms of muscle-relaxant effects of zopiclone.…”
Section: Discussioncontrasting
confidence: 93%
“…Thus, the doses of zopiclone, triazolam, and nitrazepam we used are thought to be equivalent to 20 Tada/Sato/Sakai/Ueda/Kasamo/Kojima Effects of Hypnotics on Standing Steadiness Previous investigators have reported weak musclerelaxant effects of zopiclone as compared to classical ben zodiazepines in mice, rats, and cats. For instance, the muscle-relaxant effects of zopiclone were approximately 4-80 times less potent than those of nitrazepam in mice and rats [15,16], and 3.5-5 times less potent than those of diazepam in mice, rats, or cats [1], However, the present preliminary data indicating stronger muscle-relaxant ac tivities of zopiclone than of nitrazepam in humans do not support these previous animal experiments. Pharmacoki netic differences between zopiclone and nitrazepam do not seem to explain the differences between studies since our previous pharmacokinetic-dynamic study of nitraze pam indicated that peak effects of nitrazepam were ob tained at 1 and 2 h after drug administration [6,17], Thus, there seem to be great species differences in terms of muscle-relaxant effects of zopiclone.…”
Section: Discussioncontrasting
confidence: 93%
“…Conventional analgesics are expensive, have arguably many side effects such as gastric disorders, kidney, liver and heart failure, prolonged bleeding after injury and diabetes and continued use may lead to addiction and drug resistance. Almost all pharmacological treatments may produce side effects [4]. Alternative medicines are thought to posses many safe and effective phytocompounds useful in treating various disorders including pain.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional analgesics are expensive, have arguably many side effects such as gastric disorders, kidney, liver and heart failure, prolonged bleeding after injury and diabetes and continued use may lead to addiction and drug resistance. Almost all pharmacological treatments may produce side effects [5]. Medicinal plants are believed to be an important source of new chemical substances with potential therapeutic effects against pain [6,7].…”
Section: Introductionmentioning
confidence: 99%